Pengaruh Kompetensi Manajerial Kepala Sekolah terhadap Kinerja Guru di SMP Islam Al-Ulum Terpadu Medan - Rahmiatul Zuhro; Abdul Fattah Nasution; Winda Sari (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
This research aims to determine the influence of the managerial competence of school principals at Al-Ulum Integrated Islamic Middle School in Medan. This research uses a quantitative approach with descriptive methods using a questionnaire as a data collection instrument. The population in this study was 30 teachers, so the sample size in this study was 30 teachers, because the population was less than 100, based on Suharsimi Arikunto opinion, the entire population was used (population study). The main data collection technique uses a 5 Likert scale answer choice form. Data is analyzed using simple linear regression to test the research hypothesis. Based on the data processing carried out statistical testing resulted in Ho being rejected and Ha being accepted, which explains that there is an influence of the principal's managerial competence on teacher performance. This is obtained from the result of the Pearson correlation test which shows that the value is 0.512 > tubel 0.361 and the results of the simple linear regression test produce contribution Y’ = 100.242 + 0.322 X, so the results of this test explain that there is a correlation between the managerial comptence of school principals and teacher performance.apart from that, tests are carried out T-test which produced a t-count of 3.157 > t-table, namely 2.048, with a significance value of 0.004 < 5% (0.05). The results in the ANOVA table also support the acceptance of Ha, where the sig. 0.004 < alpha value or 0.05. So, the hypothesis simultaneously proves that there is a significant influence between the managerial competence of school principals on teacher performance. Calculation of the coefficient of determination shows that the principal's managerial competency variable is able to explain the student learning achievement variable by 26,2%. Meanwhile, the remaining 73.8% is explained by other variables not studied. From the results of these calculations, it can be concluded that there is an influence between the principal's managerial competence on teacher performance at Al-Ulum Terpadu Islamic Middle School, Medan. This influence can be seen from the school principal in making a defined plan, making decisions, organizing the resources they have, and carrying out evaluations to improve teacher performance.